Redox signaling and oxidative stress: Cross talk with TNF-related apoptosis inducing ligand activity. (December 2016) - Voltan, Rebecca; Secchiero, Paola; Casciano, Fabio; Milani, Daniela; Zauli, Giorgio; Tisato, Veronica
Abstract: Redox regulation plays a key role in several physiopathological contexts and free radicals, from nitric oxide and superoxide anion up to other forms of reactive oxygen species (ROS), have been demonstrated to be involved in different biological and regulatory processes. The data reported in the current literature describe a link between ROS, inflammation and programmed cell death that is attracting interest as new pathways to be explored and targeted for therapeutic purposes. In this light, there is also growing attention to the involvement of this link in the activity of the TNF-related apoptosis inducing ligand (TRAIL). TRAIL is a member of the TNF ligands super family able to mediate multiple intracellular signals, with the potential to lead to a range of biological effects in different cell types. In particular, the hallmark of TRAIL is the ability to induce selective apoptosis in transformed cells leaving normal cells almost unaffected and this feature has already opened the door to several clinical studies for cancer treatment. Moreover, TRAIL plays a role in several physiological and pathological processes of both innate and adaptive immune systems and of the cardiovascular context, with a strong clinical potential. Nonetheless, several issues still need to be clarified about the signaling mediated by TRAIL to gain deeper insight into its therapeutic potential. In this light, the aim of this review is to summarize the main preclinical evidences about the interplay between TRAIL and redox signaling, with particular emphasis to the implications in vascular physiopathology and cancer.